UPAYA PENINGKATAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN METODE PEMBELAJARAN GENERATIF SISWA KELAS VA SDN 004 BAGAN BESAR KECAMATAN BUKIT KAPUR - Situmeang, Ratna (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve learning outcomes Indonesian student class V SDN 004 BaganBesar through generative teaching methods. Subjects in this study were students of class VSDN 004 Bagan Besar on the subjects of Indonesian in commenting on the issue of factualmaterial. This research is a class act that is a practical research that aims to improve thedeficiencies in the classroom is one of them enhance the creativity of student learning andgeneralizing ability of students in the classroom, by undertaking certain actions in order toand improve the practices of learning in class more professionally. From observations made,improving student learning outcomes significantly. It can be seen from the first meetingbefore action is taken by the generative teaching methods, learning outcomes in the first cycle(76%) and cycled II increased to (92%). Based on the analysis it can be concluded that theapplication of generative teaching methods to improve learning outcomes graders of SDN004 Bagan Besar Kecamatan Bukit Kapur.